Die konstellasie taalbegrip-logika in die Middeleeuse filosofie (1): Augustinus tot Aquinas - Beukes, Johann (HTS teologiese studies, 2011)
The constellation language-logic in medieval philosophy (1): St Augustine to St Aquinas This series of two articles provides an in-depth overview of some of the most prominent (and some of the most underpublished) medieval thinkers’ stance on the constellation of language and logic, thus as a combined and condensed problem in Western philosophy between the 5th and 15th centuries. The articles form part of a rehabilitating series of modern-critical articles on understated and marginalised themes, texts and figures in medieval philosophy. The positions of the well-known philosophers that are covered in the two articles, St Augustine, Peter Abelard, St Thomas Aquinas, John Duns Scotus and William of Ockham, are juxtaposed with some less familiar philosophical positions, amongst others those of Boethius, Peter of Spain, John Wyclif and Peter de Rivo.